PARTISIPASI POLITIK PEREMPUAN DALAM PEMBANGUNAN ACEH PASCAKONFLIK - Cut Asmaul Husna (Universitas Teuku Umar, 2016)
After conflict aceh development much more developing and industrialized in various sectors, aceh start rise from bankruptcy economy, social and cultural, political, infrastructure. Resurrection aceh in development pascakonflik caused by participation of various parties and the in aceh, including the perempuan.studi aims to see and understand political participation daughters of development in aceh pascakonflik as learning to daerah-daerah in indonesia even negara-negara else in the world which still experience conflict or development problems in doing rekontruksi and rehabilitation after conflick.The theory of the research is theory political participation focusing on women involvement in the decision, planning, implementation, the use of the development and the evaluation aceh pascakonflik development. Studies show that women aceh have been involved active in the development , however the impact of participation in political sector is still very low against the construction of aceh .In the context of economic and political, women aceh still have a great opportunity struggling to get a reasonable rights should be equal treatment with the laki-laki in development aceh because undang-undang aceh give space all its citizens participate in development without except for .Because bias gender, where yardstick chance and ability often seen from the sexes put women position at a lower, besides the ability to improve the quality of women in an effort to their involvement through the political in aceh developmentKeywords: women, political participation aceh, development.